Digital Activism from the Perspective of NGO and Young People - Juan Sebastián Fernández-Prados (2021)
Digital resources have become a key element in understanding new processes of citizen participation. In recent years, the use of new digital technologies has intensified in the relationship between citizens and public decision-makers, as well as with various social movements and activist projects. The ability for action of civil society organisations is increasingly linked to their communication strategies in the online environment, especially when it comes to attracting and involving the younger generations. The aim of this research is to understand what elements ease or hinder the smooth digital participation of young Andalusians in a specific sector of organisations: The Third Sector Social Action entities using in their autonomous community. To analyse this, we resorted to a combination of several qualitative techniques. We examined the adaptation to new communication technologies and network strategies of a sample of organisations by means of in-depth interviews with those responsible for communication in these organisations. On the other hand, we analysed the discourse of the potential audience of their communication strategies, through discussion groups with young people with cyberactivist experiences and active profiles in social networks. The results show various obstacles to the existence of effective digital participation. On the part of the organisations, there is a tendency to prioritise "street work" over online strategies, which continue to be understood as a field limited to communication professionals, and not as a transversal element in the organisation's activity. Young activists perceive this type of organisation as excessively institutionalised and with demands that are far removed from their day-to-day problems.